Deep roots, open skies : new biology in India : a festschrift in honour of Dr. (Mrs.) Manju Sharma - Basu, Sandip K.; Batra, Janendra K.; Salunke, Dinakar M.; Sharma, Manju (New Delhi : Narosa Pub. House, 2004)
Festschrift for Manju Sharma, b. 1940, Indian botanist; contributed papers presented in a one-day symposium at National Institute of Immunology, New Delhi, India.
Includes bibliographical references and index.
Keywords: Biotechnology -- Research -- India; Biology -- Research -- India; Agricultural biotechnology -- Research -- India; Medical sciences -- Research -- India